Significance of the organic aerosol driven climate feedback in the boreal area - Taina Yli-Juuti (Nature Portfolio, 2021)
Vegetation emits organic vapors which can form aerosols in the atmosphere and influence cloud properties. Here, the authors show observational evidence that warmer temperatures lead to increased emissions of these aerosols in boreal forests which cause surface cooling, demonstrating a negative climate feedback mechanism.